Prevalence of Posttraumatic Stress Symptomatology and Distribution of Attachment Patterns 1 and 5 Months after a Terrorist Attack (Journal Of Educational and Psychological Researches, 2017)
As a consequence of a terrorist attack, people may experience posttraumatic stress disorder (PTSD) and lack of feeling secure in relationships. This longitudinal study aimed to examine the prevalence of PTSD symptoms over time, the relationship between adult attachment styles and PTSD, as well as their association with degree of exposure, and finally to consider the distribution and the trajectory of attachment styles. The sample consisted of 235 students (M=125, F=110) who were exposed to different levels of trauma intensity in response to a bombing attack. Participants were recruited and assessed approximately 1 month and 5 months after the attack using a battery of questionnaires. Findings revealed, as expected, that 79.5% of the participants met the criteria for current probable PTSD and 78.2% endorsed one of the three insecure attachment dimensions at baseline, which declined over time. Correlational analyses revealed a significant positive relationship between intensity of exposure and both PTSD symptoms and insecure attachment. The results confirm and extend previous findings on the association between direct exposure to life-threatening situation and the risk of behavioural and emotional problems among civilians, which may present as non-specific psychopathology.